2020
DOI: 10.1186/s41182-020-00239-2
|View full text |Cite
|
Sign up to set email alerts
|

Socio-demographic factors of cesarean births in Nha Trang city, Vietnam: a community-based survey

Abstract: Background The cesarean section rate in Vietnam has been increasing especially in urban area. However, limited evidence identified regarding socio-demographic factors of the cesarean section birth. The objective of this study was to determine the current cesarean birth rate and the associated socio-demographic factors among mothers in Nha Trang city, south-central Vietnam. Methods A community-based cross-sectional study was conducted between October and November in 2016… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 28 publications
3
6
0
Order By: Relevance
“…The caesarean section rate in current study is also higher than the rate of caesarean section rate of 27.5% in Vietnam from 2011 to 2014 reported by UNICEF [ 2 ] and average caesarean section rate of 15.9% in South-eastern Asia [ 2 ]. However, this rate is consistent with the rate reported in urban areas in Vietnam of study 2018 (58.6%) [ 4 ] and 2020 (44.3%) [ 11 ]. Our study was conducted in two first class cities in Vietnam and both cities are among the ten largest cities in Vietnam.…”
Section: Discussionsupporting
confidence: 91%
“…The caesarean section rate in current study is also higher than the rate of caesarean section rate of 27.5% in Vietnam from 2011 to 2014 reported by UNICEF [ 2 ] and average caesarean section rate of 15.9% in South-eastern Asia [ 2 ]. However, this rate is consistent with the rate reported in urban areas in Vietnam of study 2018 (58.6%) [ 4 ] and 2020 (44.3%) [ 11 ]. Our study was conducted in two first class cities in Vietnam and both cities are among the ten largest cities in Vietnam.…”
Section: Discussionsupporting
confidence: 91%
“…Mothers were more likely to have cesarean section at higher parity, mostly because of prior cesarean section. Prior cesarean section was the most common reason for having a repeated one, as we found in this study and other studies in Vietnam [ 15 , 18 ], and other countries [ 34 , 35 ]. Vaginal delivery after cesarean is a reasonable and safe choice for the majority of women with prior cesarean [ 36 ].…”
Section: Discussionsupporting
confidence: 83%
“…We selected other potential covariates purposively from a review of the literature [ 14 , 15 , 16 , 17 , 18 , 19 , 27 , 28 , 29 ]. Socioeconomic position (maternal education) and demography (maternal age, parity, history of fetal loss) were extracted from the baseline survey.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A study from Da Nang, the third largest city in Vietnam, reported a c-section rate of 58% in public hospitals and 70% in private hospitals [39]. Another study from Nha Trang, a tourist city in southern Vietnam, reported a c-section rate of 44% [40]. The high proportion of emergency c-sections at Phu San Hanoi Hospital might indicate a lower-than-average threshold for converting an unsatisfactory vaginal delivery progress to c-section.…”
Section: Discussionmentioning
confidence: 99%